Persistent Mullerian Duct Syndrome Presented as Male Infertility, a Case Report - Roopak Aggarwal; Pinki Pandey; Anubhav Gautam; Sanjeev Kumar Singh; Md. Mubashir Ali Khan; Harender Kumar (Advancement and New Understanding in Medical Science Vol. 1, 2024)
Introduction: Transverse testicular ectopia associated with persistent mullerian duct syndrome (PMDS) is a rare form of male pseudo hermaphroditism usually unexpectedly found at surgery for cryptorchidism. Case Presentation: An adult male, presented with complaints of primary infertility and inguinoscrotal swelling. USG shows hernial defect protruding into the scrotum on one side and the testis absent on the contralateral side. Intraoperative findings were of undescended testis both present on left inguinal region with uterus and both the fallopian tubes. Histopathological and karyotyping findings confirm the diagnosis of persistent mullerian duct syndrome. Conclusion: Familiarity of the operation surgeon with this disease condition would increase the chances of correctly diagnosing and appropriately dealing with mullerian duct remnants.